2017
DOI: 10.1186/s13075-017-1227-y
|View full text |Cite
|
Sign up to set email alerts
|

α2AP regulates vascular alteration by inhibiting VEGF signaling in systemic sclerosis: the roles of α2AP in vascular dysfunction in systemic sclerosis

Abstract: BackgroundSystemic sclerosis (SSc) is a connective tissues disease of unknown origin characterized by vascular damage and extensive fibrosis. Recently, we demonstrated that α2-antiplasmin (α2AP) is associated with the development of fibrosis in SSc. We herein investigate the roles of α2AP in vascular dysfunction in SSc.MethodsVascular damage in mice was determined by the levels of blood vessels and blood flow. Vascular functions in vascular endothelial cells (ECs) were determined by the levels of tube formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…VEGF exists in endothelial cells and various non‐endothelial cells . Without doubt, VEGF is mainly expressed in endothelial cells including umbilical vein endothelial cell, retinal pigmentary epithelial cells, bronchial, alveolar epithelial cells and so on . Moreover, the tube formation of HUVECs was commonly performed to evaluate the angiogenesis activity in skin wound healing .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…VEGF exists in endothelial cells and various non‐endothelial cells . Without doubt, VEGF is mainly expressed in endothelial cells including umbilical vein endothelial cell, retinal pigmentary epithelial cells, bronchial, alveolar epithelial cells and so on . Moreover, the tube formation of HUVECs was commonly performed to evaluate the angiogenesis activity in skin wound healing .…”
Section: Discussionsupporting
confidence: 66%
“…As well as we know, VEGF is mainly expressed in endothelial cells . Next, the effect of NaHS on tube formation of HUVECs was investigated to evaluate the activity of blood formation in vitro.…”
Section: Resultssupporting
confidence: 47%
“…uPAR is involved in the high-molecular-weight kininogen (HKa)-mediated apoptoic effect [110]. α2AP induces vascular damage, such as the reduction of blood vessels and blood flow in mice, and α2AP neutralization improves vascular damage in SSc model mice [33]. In addition, α2AP is associated with vascular remodeling and EC apoptosis [57].…”
Section: The Role Of Fibrinolytic Regulators In Vascular and Ec Inmentioning
confidence: 99%
“…Furthermore, uPAR-deficient mice develop vasculopathy [8]. α2AP induces vascular injury, and α2AP deficiency attenuates the SSc-associated vascular dysfunction in SSc model mice [33]. These fibrinolytic regulators may be associated with the SSc-associated vascular disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Alpha2-antiplasmin (α2AP) is known to be the principal inhibitor of plasmin, resulting in the formation of a stable inactive complex, plasmin-α2AP (PAP), and inhibits fibrinolysis and ECM degradation [6][7][8]. α2AP is synthesized in various tissues; has various functions, such as cytokine production, cell growth, and cell differentiation; and regulates angiogenesis, inflammatory response, immune modulation, tissue repair, bone formation, and brain functions [9][10][11][12][13][14][15][16][17][18]. Many studies have reported that the levels of PAP in plasma are elevated in fibrotic diseases which include systemic sclerosis (SSc), diabetic nephropathy, liver cirrhosis, and rheumatoid arthritis [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%